Hydrogen Energy Storage: New Techno-Economic Emergence Solution Analysis. (August 2015) - Becherif, M.; Ramadan, H.S.; Cabaret, K.; Picard, F.; Simoncini, N.; Bethoux, O.
Abstract: The integration of various renewable energy sources as well as the liberalization of electricity markets are established facts in modern electrical power systems. The increased share of renewable sources within power systems intensifies the supply variability and intermittency. Therefore, energy storage is deemed as one of the solutions for stabilizing the supply of electricity to maintain generation-demand balance and to guarantee uninterrupted supply of energy to users. In the context of sustainable development and energy resources depletion, the question of the growth of renewable energy electricity production is highly linked to the ability to propose new and adapted energy storage solutions. The purpose of this multidisciplinary paper is to highlight the new hydrogen production and storage technology, its efficiency and the impact of the policy context on its development. A comprehensive techno/socio/economic study of long term hydrogen based storage systems in electrical networks is addressed. The European policy concerning the different energy storage systems and hydrogen production is explicitly discussed. The state of the art of the techno-economic features of the hydrogen production and storage is introduced. Using Matlab-Simulink for a power system of rated 70 kW generator, the excess produced hydrogen during high generation periods or low demand can be sold either directly to the grid owners or as filled hydrogen bottles. The affordable use of Hydrogen-based technologies for long term electricity storage is verified.